Cellulose Nanofibers-Graphene Nanoplatelets Hybrids Nanofillers as High-Performance Multifunctional Reinforcements in Epoxy Composites. Issue 4 (May 2017) - Nuruddin, Md.; Hosur, Mahesh; Gupta, Raju; Hosur, Gaurav; Tcherbi-Narteh, Alfred; Jeelani, Shaik
The objective of this study was to fabricate epoxy polymer composites modified with cellulose nanofibers (CNFs) and graphene nanoplatelets (GNPs) binary filler materials. Individual (0.2 wt.% GNPs or 2 wt.% CNFs) and binary nanofillers (mixture of 0.5 wt.% CNFs and 0.1% GNPs) were incorporated into an epoxy matrix system to investigate the synergistic effect of nanofillers on composites properties. Dynamic mechanical analysis (DMA) and three point bend tests were carried out to investigate the viscoelastic and flexural properties of neat epoxy and nanofiller-reinforced nanocomposites. Incorporation of binary nanofillers resulted in better flexure strength, modulus and storage modulus although there was no significance change in glass transition temperature (Tg ). FTIR analysis was carried out to study the probable reaction mechanism of epoxy polymer with binary nanofillers. SEM images of the fracture surface of the samples revealed rougher failure surfaces for nanophased samples.